2010
DOI: 10.4314/wiojms.v8i1.56675
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bait Usage in the KwaZulu-Natal Linefishery, South Africa

Abstract: Bait usage in the KwaZulu-Natal recreational and commercial linefishery was assessed using historic fisher-derived data and current sales records of bait providers. Total bait usage in two of the three linefishery components in KZN was estimated to range from 928 -3,400 tonnes per year. A total of 39 different bait types were identified to have been used in the KZN linefishery, and sardines (Sardinops sagax) sourced from the South African purse-seine fleet, were the most important (used in >79% of fisher outin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…more rocky surf-zone habitat sampled in the former surveys) and not because of a change in stock abundance (Mann et al 2002a). Furthermore, the catchability of N. lithophilus is low due to its herbivorous diet (Joubert 1981b), and most anglers use sardine as bait (Mann et al 2002a, Pradervand andFennessy 2009). Mann et al (2002a) showed that the spawner-biomass-per-recruit for N. lithophilus was at 46% of its pristine level, indicating that the stock is being sustainably exploited in KZN.…”
Section: Total Catch and Catch Compositionmentioning
confidence: 99%
“…more rocky surf-zone habitat sampled in the former surveys) and not because of a change in stock abundance (Mann et al 2002a). Furthermore, the catchability of N. lithophilus is low due to its herbivorous diet (Joubert 1981b), and most anglers use sardine as bait (Mann et al 2002a, Pradervand andFennessy 2009). Mann et al (2002a) showed that the spawner-biomass-per-recruit for N. lithophilus was at 46% of its pristine level, indicating that the stock is being sustainably exploited in KZN.…”
Section: Total Catch and Catch Compositionmentioning
confidence: 99%
“…Those permits were granted in order to assess the viability of a fishery for E. wongratanai and the handful of permit holders have subsequently caught only small quantities of fish annually (1–2 t: van der Lingen et al, ) . Etrumeus wongratanai is highly desired as bait by local line‐fishers, but as it cannot be targeted by commercial fishers, catches have to date been illegal (Pradervand & Fennessy, ).…”
Section: Introductionmentioning
confidence: 99%